2006
DOI: 10.1117/12.645121
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic molecular imaging of small animals in vivo

Abstract: Molecular imaging is a newly emerging field in which the modern tools of molecular and cell biology have been married to state-of-the-art technologies for noninvasive imaging. The study of molecular imaging will lead to better methods for understanding biological processes as well as diagnosing and managing disease. Here we present noninvasive in vivo spectroscopic photoacoustic tomography (PAT)-based molecular imaging of αvβ3 integrin in a nude mouse U87 brain tumor. PAT combines high optical absorption contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…As well as clinical imaging, the technique also has potential as a small animal imaging modality. A variety of studies [10 -12] have shown that high-resolution anatomical and functional images of the vasculature in the rat or mouse brain and other organs can be obtained and it has been suggested that, by using targeted optically absorbing contrast agents, the technique may also find application as a molecular imaging modality [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As well as clinical imaging, the technique also has potential as a small animal imaging modality. A variety of studies [10 -12] have shown that high-resolution anatomical and functional images of the vasculature in the rat or mouse brain and other organs can be obtained and it has been suggested that, by using targeted optically absorbing contrast agents, the technique may also find application as a molecular imaging modality [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…To date, PA contrast agents targeting angiogenesis have been designed around integrin-targeted indocyanine green (ICG)-fluorescent-peptide conjugates (27,28,34,36,37). Unfortunately, these agents easily diffuse from the neovascular vasculature, where numer-ous cell types, including macrophages (38), platelets (39), lymphocytes (39), smooth muscle cells (40), and tumor cells (41,42), express ␣ v ␤ 3 -integrin.…”
Section: Discussionmentioning
confidence: 99%
“…Xie et al 38 have demonstrated PAI of targeted glioblastoma cells in vivo in a mouse model. They have used peptide-conjugated ICG for targeting α v β 3 integrin, known to be overexpressed in gliblastoma cells.…”
Section: Brain Tumor Imaging By Icg-α α V β β 3 Targetingmentioning
confidence: 98%